Odpowiedzi

Najlepsza Odpowiedź!
2010-01-10T21:52:09+01:00
1/9*3⁻⁶*3⁴......3⁻²*3⁻⁶*3⁴..........3⁻⁴
---------------- = -------------- = ------------ = 1
(1/9)²................3⁻⁴..............3⁻⁴
2010-01-10T21:53:02+01:00
9 ⁻¹ × 27⁻² ×√9⁴::::::::::1/9 x 1/27² x 81x:::::::::1/27² x 81x::::::::::
------------------- =:::::-------------------------: =::---------------- =::::::
(jedna dziewiąta)²:::::::::::::(1/9)²;::::::::::::::::::1/9:::::::::::::::


= 1/27² x 9x =1/81 x


(dwukropki zamiast spacji)
mam nadzieje, ze sie nie pomylilem
2010-01-10T21:56:21+01:00
Nie wiem czy te √9⁴ ,,, czy ta 4 jest też pod pierwiuastkiem

== w liczniku; 3⁻³×3⁻⁶×3⁴
w mianowniku: 9⁻²
= 3⁻⁵:3⁻⁴=3⁻¹=⅓